S∗p‐b-Partial Metric Spaces with some Results in Common Fixed Point Theorems. (15th May 2021) - Zidan, A. M.
Abstract : In this paper, we introduce the notion of S ∗ P ‐ b -partial metric spaces which is a generalization each of S ‐ b -metric spaces and partial-metric space. Also, we study and prove some topological properties, to know the convergence of the sequences and Cauchy sequence. Finally, we study a new common fixed point theorem in these spaces.